Emerging periodate-based oxidation technologies for water decontamination: A state-of-the-art mechanistic review and future perspectives. (1st December 2022) - Niu, Lijun; Zhang, Kaiting; Jiang, Linke; Zhang, Menglu; Feng, Mingbao
Abstract: With the ever-increasing severity of the ongoing water crisis, it is of great significance to develop efficient, eco-friendly water treatment technologies. As an emerging oxidant in the advanced oxidation processes (AOPs), periodate (PI) has received worldwide attention owing to the advantages of superior stability, susceptible activation capability, and high efficiency for decontamination. This is the first review that conducts a comprehensive analysis of the mechanism, pollutant transformation pathway, toxicity evolution, barriers, and future directions of PI-based AOPs based on the scientific information and experimental data reported in recent years. The pollutant elimination in PI-based AOPs was mainly attributed to the in situ generate reactive oxygen species (e.g., OH, O( 3 P), 1 O2, and O2 - ), reactive iodine species (e.g., IO3 and IO4 ), and high-valent metal-oxo species with exceptionally high reactivity. These reactive species were derived from the PI activated by the external energy, metal activators, alkaline, freezing, hydroxylamine, H2 O2, etc. It is noteworthy that direct electron transport could also dominate the decontamination in carbon-based catalyst/PI systems. Furthermore, PI was transformed to iodate (IO3 − ) stoichiometrically via an oxygen-atom transfer process in most PI-based AOPs systems. However, the production of I2, I −, and HOI was sometimes inevitable. Furthermore, the transformation pathway of typical micropollutants was clarified, and the in silico QSAR-based prediction results indicated that most transformation products retained biodegradation recalcitrance and multi-endpoint toxicity. The barriers faced by the PI-based AOPs were also clarified with potential solutions. Finally, future perspectives and research directions are highlighted based on the current state of PI-based AOPs. This review enhances our in-depth understanding of PI-based AOPs for pollutant elimination and identifies future research needs to focus on the reduction of toxic byproducts. Graphical abstract: Image 1 Highlights: PI-based AOPs can produce various active species for pollutant elimination. The treated water using PI-based AOPs was mostly assayed as non-toxic. The major barriers and potential solutions were proposed for PI-based AOPs. Future research directions should aim at the scale application of PI-based AOPs.